Indonesian Monetary Regulation Regarding Chinese Electronic Payment in Indonesia - Claudia Mulyawan; Emmy Latifah (Faculty of Law, Jambi University, 2019)
This article aims to analyze and ﬁnd the answer on how the regulation for transaction activities deals with electronic money by Chinese tourists in Indonesia, especially in Bali, as well as to analyze the effect on using WeChat Pay and Alipay payment in tourism sector. This legal research is using normative research method. It is concluded that Chinese electronic payment platform WeChat Pay and Alipay by Chinese tourists for doing payment transactions in Bali has not been explicitly regulated in Indonesia because those providers have not fulﬁlled any requirements and standards from Indonesian Central Bank (Bank Indonesia) and have not obtained any Indonesian legal status as a private company. Transactions using Chinese electronic also have impact for the country’s foreign exchange reserves. Foreign exchange reserves is one of the important aspect in deciding the value of state budget (APBN) that is also inﬂuenced by foreign exchange reserves from tourism sector.